2016
DOI: 10.1182/blood-2015-12-688960
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic mutations in the cytotoxicity pathway increase susceptibility to develop HLH immunopathology in mice

Abstract: Key Points• The accumulation of monoallelic mutations in HLH-causing genes impairs lymphocyte cytotoxicity contributing to HLH immunopathology in mice. • A polygenic model may account for some of the cases of secondary HLH observed in humans.Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory disease. Inherited forms of HLH are caused by biallelic mutations in several effectors of granule-dependent lymphocyte-mediated cytotoxicity. A small proportion of patients with a so-called "s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Heterozygous mutations that each partially impair cytotoxic function may generate a 'gene dosage' effect through synergy (Zhang et al, , 2014a. This was corroborated by the generation of polygenic mouse models, in which the accumulation of heterozygous mutations in Rab27a, Prf1 and/or Stx11 reduced cytotoxic function and increased the risk of developing virus-induced HLH (Sepulveda et al, 2016). Heterozygous mutations in X-linked genes may also cause HLH in female patients, depending on the percentage of wild-type X-chromosome inactivation (Holle et al, 2015;Yang et al, 2015).…”
Section: Genotype/phenotype Correlations In Primary Hlhmentioning
confidence: 94%
“…Heterozygous mutations that each partially impair cytotoxic function may generate a 'gene dosage' effect through synergy (Zhang et al, , 2014a. This was corroborated by the generation of polygenic mouse models, in which the accumulation of heterozygous mutations in Rab27a, Prf1 and/or Stx11 reduced cytotoxic function and increased the risk of developing virus-induced HLH (Sepulveda et al, 2016). Heterozygous mutations in X-linked genes may also cause HLH in female patients, depending on the percentage of wild-type X-chromosome inactivation (Holle et al, 2015;Yang et al, 2015).…”
Section: Genotype/phenotype Correlations In Primary Hlhmentioning
confidence: 94%
“…Three out of 31 patients (9.7%) carried a mutation in 2 genes. Interestingly, it has been recently reported that mice carrying heterozygous mutation in more than one gene involved in pHLH carry a significant higher risk to develop HLH following viral infection [16]. Overall, clinical and laboratory feature of MAS in patients carrying the mutations were not different from those of patients who do not carry the mutation.…”
Section: Introductionmentioning
confidence: 92%
“…These abnormalities occur by altering the protein variants of the various genes, including PRF1, MUNC13-14, STX11, STXBP2, LYST , and RAB27A , which are involved in the granule-mediated cytotoxic pathway 2124. Heterozygous mutations in some of these genes might be associated with the development of MAS, especially if triggered by infections 25. Moreover, hyperinflammation, especially in SJIA, results in high levels of interleukin (IL)-6.…”
Section: Pathogenesismentioning
confidence: 99%